Experimental Analysis of Surface Roughness While Drilling the Glass Fibre Reinforced Polymer Composite Materials using Response Surface Methodology - Mohan, Nanjangud; Bhat, Ritesh; M. Kulkarni, S. (International Journal of Engineering and Technology, 2018)
Drilling is the most widely used material removal process and contributes to be one of the most important processing techniques in almost all the assembly process. Composite material, in particular the glass fibre reinforced polymer composites, is an advanced family of materials, which keeps attracting the manufacturers since the marking of its existence. Drilling a glass fibre reinforced (GFR) polymer composites varies from drilling any conventional metal due to its anisotropic behavior. The article majorly focuses on optimizing theÂ  drilling process parameters viz., cutting parameters (cutting speed and feed), drill tool parameters (drill diameter) and material parameters (specimen thickness) to minimize the surface roughness. Response surface method is been used as the experimental analyzing tool to achieve the required machining quality. The results obtained clearly depicts that the chosen drill parameters significantly affects surface roughness value and optimizing the chosen parameters can enhance the machining qualityÂ Â